Ovulation and Condom Use - Lawton, Gina M.; Stone, Hilary D. (My University, 2013)
Ovulation increases women's likelihood to engage in short-term mating with highly attractive men, thus elevating the likelihood of conception with attractive men (Baker & Bellis, 1995; Bellis & Baker, 1990). Given what is suggested to be an implicit goal of (short-term) mating with highly attractive men, the purpose of this study was to determine the affect ovulation has on women's explicit condom attitudes and behaviors.
Color poster with text and graphs.
Keywords: Ovulation; Condoms; Mating; Posters